Comunidade de macroinvertebrados associados a diferentes espécies de macroalgas recifais e estuarinas no Nordeste brasileiro - Duarte, Rafaela Cristina de Souza (2019)
Macroalgae are considered essential components in marine and estuarine ecosystems because they support a range of associated organism. Habitat complexity and seasonality may be influence the abundance of fital macroinvertebrates. Macroalgal communities have their life cycles marked by temporal changes, including succession and seasonality. Studies about functional richness and functional diversity indices seek to understand the ecological roles developed by species and their interaction with the environment. In this context, the present study aims to verify the influence of the complexity of macroalgae on the associated invertebrate communities in a reef and hypersaline estuarine and understand the seasonal variations of these communities and how they are functionally structured. The research was conducted in the hypersaline estiary of Rio da Casqueira and on the reefs of Praia do Seixas, northeastern Brazil. The following questions guided this research: i) Is there influence of the habitat complexity offered by macroalgae on the composition, abundance, richness and diversity of macroinvertebrates and on the molluscs size? ii) Does the macroinvertebrate community associated with macroalgae in the estuarine environment and the size of mollusks differ to dry and rainy seasons? and iii) Is there a difference in the functional diversity and functional richness of the shellfish community in relation to the complexity of macroalgae? In both environments the most abundant macroinvertebrate groups were Amphipoda, Polychaeta, Echinodermata e Mollusca. The malacofauna was predominantly composed of micromoluscs (0.20 to 4.50 mm in length), most of them when adults do not exceed 10 mm. It was observed that in the estuarine environment there was a greater variation in the macroalgae morphology, and a difference in macrofauna abundance in the two seasonal periods analyzed. Therefore, it is suggested that both habitat complexity and seasonality affect the richness, diversity and abundance of associated communities. Besides that The positive influence of macroalgal complexity on the structure of the mollusc community and its composition of functional traits was observed, pointing out the relevance of macroalgal microhabitats and their associated organisms in the structuring of trophic chains of marine and estuarine ecosystems